Medicinal Chemistry Review Of Bioactive Compounds In Moringa Leaves (Moringa Oleifera) As Natural Antioxidants - Saeful Amin Saeful Amin; Delya Annisa Putri; Syalwa Nazmi Diki; Melvi Dwi Ariani (CV. AFDIFAL MAJU BERKAH, 2026)
Moringa oleifera leaves are widely used in the health sector due to their rich content of bioactive compounds with potential as natural antioxidants. Secondary metabolites such as flavonoids, polyphenols, alkaloids, tannins, saponins, steroids, and triterpenoids play an important role in scavenging free radicals and protecting cells from oxidative damage. This article aims to review the potential of bioactive compounds in Moringa oleifera leaves as antioxidants from a medicinal chemistry perspective. The study was conducted using a literature review method by analyzing national and international scientific articles published between 2020 and 2026 from Google Scholar, PubMed, and ScienceDirect databases. The findings indicate that the antioxidant activity of Moringa oleifera leaves is mainly influenced by flavonoids and phenolic compounds. In addition, extraction methods, drying processes, fermentation, and formulation techniques also affect the effectiveness of antioxidant activity. Several studies further report that Moringa oleifera leaves have strong potential to be developed into pharmaceutical preparations and health products due to the stability of their active compounds. Overall, Moringa oleifera leaves represent a promising natural antioxidant source for further development in the field of pharmaceutical science based on natural products.